Inter-rater reliability of Böhler and Gissane angles in different calcaneal fracture according to the Essex-Lopresti and Sanders classifications - Barroco, Rui dos Santos; Miranda, Bruno Rodrigues de; Fernandes, Herbert Amantéa; Pessoa, Gregory Bittar; Nishikawa, Danilo Ryuko Cândido; Oliveira, Leticia Zaccaria Prates de; de Freitas, Álvaro Diego Pupa; Almeida, Caio Ivo de (Journal of the Foot & Ankle, 2021)
Objective: To evaluate the inter-rater reliability and intra-class correlation coefficients (ICC) of Böhler’s angle and the critical angle of Gissane in calcaneal fractures, stratified by severity and by the Essex-Lopresti and Sanders classifications. Methods: Retrospective study of radiographs obtained from 97 patients: 67 with calcaneal fractures and 30 with normal lateral radiographs (used as a control group). Böhler’s angle and the angle of Gissane were measured by six raters: two orthopedic surgery residents, two musculoskeletal radiologists, a foot and ankle surgery fellow, and a senior consultant in foot surgery. Statistical analysis of inter-rater reliability was performed for the two angles, in the sample overall and stratified by the different radiographic and CT subtypes of calcaneal fractures. Results: For the angle of Gissane, the ICC was at best 0.400 (95% CI: 0.250 to 0.581) for normal radiographs, with poor agreement across all classifications and severity stratifications. For Böhler’s angle, the ICC values indicated weak to moderate agreement, with the best reproducibility obtained for the overall sample (0.740; 95% CI: 0.673 to 0.801). In Sanders type 1 fractures, the ICC was 0.704 (95% CI: 0.397 to 0.940), and in Sanders type 2 fractures, 0.762 (95% CI: 0.634 to 0.870). Conclusion: Böhler’s angle is more reproducible than the critical angle of Gissane, with greater inter-rater reliability among fractures deemed less severe on the Sanders classification, although the overall ICC ranged from weak to moderate at best. Level of Evidence III; Case Control Study; Diagnostic Studies.